Genotype X environment interaction and stability analysis in upland rice (Oryza sativa L.) varieties in Ethiopia - Abebe, D.; Mohammed, W.; Abebe, A.T. (Springer, 2023)
Determination of the genotype x environment interaction (GEI) and stability of upland rice varieties for grain yield provides the basis to identify high-yielding and stable upland rice varieties across different environments and to delineate and identify rice mega environments in Ethiopia. Twenty rice varieties were laid out in a randomized complete block design with three replications and evaluated across six locations that represent the major rice growing agro-ecologies in the country. The combined analysis of variance over environments revealed significant differences among genotypes, environments and GEI for grain yield. The significant GEI implicated the differential response of the genotypes in different environments and demonstrated the remarkable effect of GEI on the performance of the genotypes. The partitioning of GEI based on the AMMI model revealed that only the first two terms of AMMI were significant. The E and GEI had a higher contribution than G for most of the traits, and GEI had larger contribution than G and E to the variations in the studied varieties for yield. The Interaction Principal Component Axis one (IPC1) and two (IPC2) contributed to 55.1% and 24.8% of the GEI sum of squares, respectively. NERICA-3, Hidasse and Chewaqa varieties were identified as responsive to changing environments and the first three best varieties across poor to most favorable environments. NERICA-12 and ADET were identified as the most stable and widely adapted varieties based on most of the stability parameters. NERICA-4, NERICA-13 and Getachew varieties were identified as stable varieties by most of the stability parameters and selected as the first three best varieties at poor to average environments. In conclusion, this study revealed that GE interactions were an important source of rice yield variation, and its AMMI biplots were forceful for visualizing the response of genotypes to environments.